Floral biology of Eriope blanchetii (Lamiaceae) in coastal sand dunes of NE Brazil - DA SILVA, FABIANA O.; VIANA, BLANDINA F.; JACOBI, CLAUDIA M. (Austral ecology, 2005)
The floral biology of the sand dune shrub Eriope blanchetii (Benth) Harley was investigated in a wild population located within an environment protection area near Salvador, NE Brazil. Inflorescence and flower development were monitored, and the reproductive biology was assessed. Inflorescences are terminal panicles, each bearing from one to 38 small, zygomorphic flowers. The duration of an inflorescence is about 2 months, with few new flowers each day. The rewards to visitors are pollen and nectar, the latter being produced in small quantities at the corolla base, near the stylopodium. Three sequential phases of flower development were identified, based on colour changes, pollen and nectar availability, and stigmatic receptivity. Anthesis takes place throughout the day within each plant, and flowers are strongly protandrous. Flowers are short‐lived, with individual variations of 7–30 h until corolla abscission. This variation is probably associated to a post‐pollinating response, which reduces the length of the female phase and could be advantageous for the economy of nectar production and for increased efficient pollination of the remaining flowers on a plant. The results of the pollination tests (apomixis, spontaneous and manual autogamy, manual cross‐pollination, and control) reinforced the role of pollinators for the reproductive success of E. blanchetii, given that the production of fruits from spontaneous pollination is unlikely to be resulting from protandry and given the morphological floral features. Taken together, the morphological and physiological aspects of E. blanchetii floral biology favour cross‐pollination, and it is likely that most of the fruits in nature are produced by outcrossing.